The shallows [videorecording (DVD)] - Jaenada, Óscar, 1975-; Lively, Blake; Cullen, Brett (Sony Pictures Home Entertainment, 2016)
Nancy is surfing on a secluded beach, and finds herself on the feeding ground of a great white shark. Though she is stranded only 200 yards from shore, survival proves to be the ultimate test of wills, requiring all of Nancy's ingenuity, resourcefulness, and fortitude.